Value of rice mill feed as a feedstuff for backgrounding heifers - Brazle, F.K.; Coffey, K.P. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Stocker heifers were fed diets of either 67% rice mill feed + 33 % dehydrated alfalfa pellets (RA) or a 67% grain sorghum + 33% dehydrated alfalfa pellets (GA). The RA heifers consumed more feed daily but gained slower (P<.05), resulting in poorer feed efficiency. RA heifers also had a lower percentage shrink (P<.05) during the first 2 1/2 hr of simulated trucking. Rice mill feed is a poor feedstuff for growing calves when included in rations at high levels.
Keywords: Beef; By-products; Rice mill feed; Backgrounding